Successful myomectomy during pregnancy for the indication of acute lower abdominal pain with red degenerative myoma or ovarian torsion? “Case report” - Leta Hinkosa Dinsa; Amenu Diriba Eticha; Mathewos Tamene Terefe (SAGE Open Medical Case Reports)
Uterine fibroids are benign tumors, arising from uterine smooth muscle cells. They are one of the most common benign tumors of the female genital tract among childbearing women, occurring in 20%–50% of women of reproductive age. The association of uterine myomas with pregnancy is high. This occurrence is constantly increased, linked to the onset of pregnancies, leading to the incidence of myomas gradually rising with age, hence the emergence of ultrasound reveals during routine ultrasound examinations of pregnancies, that were previously asymptomatic. Myomectomy during the second trimester was done and pregnancy continued safely to the third trimester. After successfully repairing it, the pregnant woman followed her antenatal care at Wollega University Referral Hospital, Western Oromia, Ethiopia. We presented the 20-year-old primigravida lady with a complaint of lower abdominal pain and a slight fever. We found a non-pedunculated, attached to the uterus via a broad base) myoma measuring 4 × 4 cm on 2D pelvic ultrasound. We admitted the client and gave her conservative management after we put her on antibiotics. Despite antibiotics, the pain persists we decided to manage it through an operation after we counseled the client about the potential complications. Then we removed the myoma without manipulating the uterus and it was a successful myomectomy without complicating the fetomaternal conditions. Currently, fetomaternal conditions are safe, and the woman is following her antenatal care at Wollega University’s Referral Hospital. In the majority of cases of women with fibroids, pregnancy comes with complications, according to literature data, The coexistence of the myoma with pregnancy: increased frequency of spontaneous abortions and premature births, increased risk of bearing ablation, higher incidence of maternal-fetal incommunicability, incorrect position of the fetus, more often performed cesarean surgery, higher probability of postpartum hemorrhage. Prenatal myomectomy can be safely performed in the first and second trimesters of pregnancy; however, it is recommended to deliver the baby via cesarean section, due to fear of intrauterine rupture of the uterus.